Phosphorus binding with ferric citrate is associated with fewer hospitalizations and reduced hospitalization costs. (June 2015) - Rodby, Roger; Umanath, Kausik; Niecestro, Robert; Jackson, James H; Sika, Mohammed; Lewis, Julia B; Dwyer, Jamie P
<x xml:space="preserve">Abstract</x> Background: Ferric citrate (FC) is a new phosphorus binder shown to increase serum iron stores while reducing intravenous iron and erythropoiesis-stimulating agent usage. Such reductions could lower hospitalization rates and associated costs. Methods: Hospitalizations during a Phase III trial were compared between FC and active control (AC). Hospitalization costs were estimated using the 2013 US Renal Data System Annual Data Report. Results: 34.6% of FC patients were hospitalized at least once versus 45.6% of the AC group (risk reduction 24.2%; p = 0.02). There were 181 unique hospitalizations in the FC group versus 239 in the AC group, for a difference of 58 hospitalizations. Total potential savings was US$ 867, 622 in hospitalization costs in the FC group. If the hospitalization reduction in our study was applied to the general end-stage renal disease population, this could translate into a savings of US$ 3002/patient/year. Conclusions: Patients receiving FC experienced fewer hospitalizations with the potential for significant savings.